Analisis Komparasi Kandungan Vitamin Anggur Laut (Caulerpa lentillifera) Antara Hasil Budidaya Terkontrol Dengan Hasil Dari Alam - Syahputro, Ichsan; Martini, Ni Nyoman Dian; Amelia, Jasmine Masyitha; Antara, Kadek Lila (Universitas Bangka Belitung, 2024)
Seaweed has various genera, one of which is the Caulerpa genus or known as sea grapes. This research aims to determine the highest content of vitamins A, C, and E in Caulerpa lentillifera between cultivation and nature. The HPLC content test results detected in cultivated C. lentillifera were only vitamin E with a content value of 0.97 mg/100 gr, while vitamin A and vitamin C could not be detected. The HPLC test results for vitamin content in C. lentillifera from nature detected vitamin A with a value of 57.07 mg/100 gr and vitamin E 0.86 mg/100 gr, while vitamin C content could not be detected. Air quality parameters in cultivation ponds range from 27-31℃, pH 7.9-9.7, salinity 29-33 ppt, nitrate 0.1-2.5 mg/l and phosphate 0.1-2.0 mg/l. Parameters in the water of the Serangan area range from temperature 28-31℃, pH 9.0-10.3, salinity 30-32 ppt, nitrate 0.1-0.2 mg/l, and phosphate 0.1-0.5 mg/l.